Beyond 400 Gbps: Reaching for Higher Data Rates and Connectivity. Issue 6 (2nd November 2019) - Hodara, Henri; Skaljo, Edvin
ABSTRACT: In this paper, we discuss in details information and communication developments (1) that have arisen in support of a rapidly expanding internet (Internet of Things, IoT) coupled with a proliferation of data centers; (2) the ensuing data rates explosion capable of reaching 800 Gb/s with coherent technology over a single wavelength; as well as (3) an increased connectivity through 5G transport networks.